Patterns of rhetorical moves and use of hedges and boosters in editorials of two newspapers - Zarza, Sahar (2016)
An editorial in a newspaper is a popular genre targeting general public as its discourse community. It plays an influential role as it presents the official position of the newspaper on a topic that is considered to be of particular societal importance. To carry the message through effectively to the public, the editors’ awareness of the generic prototypical pattern and rhetorical moves employed in editorial writings is essential, yet few studies have been done to investigate the rhetorical structure of editorials and determine their persuasive style. Furthermore, despite the effective functions of hedges and boosters in persuading readers, studies that address them are limited. Based on the belief that each writing genre has its own unique rhetorical conventions and linguistic features to engage its readers, this study aims to compare the generic characteristics and the use of hedges and boosters in the editorials of The New York Times (NYT) and New Straits Times (NST). The reason for choosing these two newspapers was that both,the NYT and NST are among the most circulated, largest and oldest newspapers in the USA and in Malaysia. They similarly have daily editorials that provided sufficient number of data and are not devoted to a particular field like business (e.g., Wall Street). To realize the objectives, a mixed method was adopted in the study to investigate both at the macro and micro levels of the 240 (NYT: n=120; NST: n=120) randomized editorials which were published in 2013. The qualitative analysis provided an in depth xamination of the use of the various rhetorical moves and steps as well as the function and linguistic realizations of hedges and boosters that were present in the two differentcorpora of editorials. To complement the qualitative analysis, the quantitative analysis sought to compare and contrast the frequency of use of both the rhetorical moves and the use of hedges and boosters in both types of editorials. The findings revealed that American and Malaysian editorials share a similar macro-structure at the move level including four obligatory moves. However, at the step level of all the moves, evidences of significant disparity of the style of writing were apparent. The results revealed higher density of steps that provide information (e.g., Addressing issue, Elaborating issue, Explaining) in the NST and higher density of those steps that illustrate the writer’s stance (e.g., Presenting standpoint, Evaluating, Raising suggestion and Expressing prediction) in the NYT. These differences indicate that the NYT editorials are mostly independent and evaluative, while the NST editorials are more informative. Moreover, at the micro-level the results revealed that both types of newspapers prefer the use of hedges to boosters in editorials. Furthermore, it was revealed that hedges in the NYT editorials were less frequent than their Malaysian counterpart, while boosters in the NYT were more frequently used than in the NST. This reveals that it is a convention in editorials to be tentative in expressing their view point, while in comparison NYT seems to be more bold, and certain in expressing its stance than NST that is more tentative. These differences could indicate cultural and contextual preferences in employing one category rather than another. In addition, in the NYT hedges and boosters were predominantly found in the third move (Justifying or refuting events) while in the NST move three (Justifying or refuting events) was prevalently hedged and boosters were predominantly found in the last move (Articulating position). Moreover, in both the NYT and NST Elaborating issue in move two, Explaining in move three and Raising suggestion in move four were the steps in which the most hedges and boosters were identified. This distribution could be due to the nature and communicative purpose of each move. To conclude, the study of hedges and boosters in the rhetorical moves of editorials is important as it would have significant pedagogical contribution especially in ESP writing classes.